Feasibility of performing non-contrast magnetic resonance angiography in pregnant subjects with familial aortopathies. (1st October 2017) - Moody, William E.; Pickup, Luke; Plunkett, Emma; Fryearson, John; Clift, Paul F.; Katie Morris, R.; Thompson, Peter J.; Thorne, Sara; Hudsmith, Lucy E.
Abstract: Background: Pregnancy is associated with an increased risk of aortic pathology. We sought to assess the feasibility of performing non-contrast 3D steady-state free-precession (SSFP) magnetic resonance angiography (MRA) in pregnant subjects with inherited aortopathy. Methods: Fifteen pregnant subjects (age 27 ± 4 yr) with positive genotyping for aortopathy (Marfan, Loeys-Dietz, Ehlers-Danlos) and/or a family history of aortic dissection underwent non-contrast 3D-SSFP MRA at 1.5 T (Avanto, Siemens Healthcare, Erlangen, Germany) using a modified ECG-triggered orientated in a sagittal-oblique plane with a respiratory navigator at the diaphragmatic level (mean acquisition time 4.1 ± 1.9 min). Imaging was performed during the mid-trimester (21 ± 5 weeks). Image analysis was performed off-line using Cvi42 software (Circle Cardiovascular Imaging, Calgary, Canada). An assessment of image quality (score 0–3) was made before performing inner edge to inner edge measurements of the thoracic aorta at 7 levels from the multiplanar reconstructions by two independent blinded observers. Results: Non-contrast 3D-MRA was successfully acquired in all 15 subjects. Image quality was deemed excellent in 87% (13/15) of cases after a mean acquisition time of 4.1 ± 1.9 min. There was a high level of agreement for aortic measurements, with low intra- and inter-observer variability (ICC ranges; 0.95–0.99 and 0.92–0.98, respectively). All pregnancies reached term (≥ 37/40) with a mean gestation at delivery of 38.0 ± 0.5 weeks. The mode of delivery was vaginal in 9 out of 15 subjects (60%). Conclusions: Non-contrast SSFP MRA imaging provides a quick and reproducible method of assessing the thoracic aorta in pregnancy.